Spinal Cord Stimulation for Refractory Angina Pectoris -A Case Report- - Lee, Seong Heon (The Korean Pain Society, 2012)
Refractory angina pectoris is defined as angina refractory to optimal medical treatment and standard coronary revascularization procedures. Despite recent therapeutic advances, patients with refractory angina pectoris are not adequately treated. Spinal cord stimulation is a minimally invasive and reversible technique which utilizes electrical neuromodulation by means of an electrode implanted in the epidural space. It has been reported to be an effective and safe treatment for refractory angina pectoris. We report a case of spinal cord stimulation which has effectively relieved chest pain due to coronary artery disease in a 40-year-old man. This is the first report of spinal cord stimulation for treatment of refractory angina pectoris in South Korea.